Effectiveness and safety of vedolizumab for ulcerative colitis: a single-center retrospective real-world study in China - Huang, Kaituo; Liu, Jing; Xia, Wenhao; Tian, Chuwen; Yao, Lingya; Cao, Qian; Chen, Haotian (Frontiers in Pharmacology, 2023)
Introduction: The effectiveness and safety of vedolizumab (VDZ) against ulcerative colitis (UC) have been validated in several randomized controlled trials and real-world studies in Western countries. However, there are few studies on VDZ in Asia, and the follow-up period for these studies is generally short. Therefore, this study evaluates the long-term effectiveness and safety of VDZ in Chinese patients with UC. Methods: This retrospective study included patients with moderate to severe UC treated with VDZ between September 2019 and April 2022 at Sir Run Run Shaw Hospital, College of Medicine Zhejiang University. Clinical response and remission were assessed using the patient reported outcomes and the partial Mayo Score, and mucosal remission and healing were assessed using the Mayo Endoscopy Score. The primary endpoint was defined as clinical remission at week 14, and secondary endpoints included clinical response and steroid-free clinical remission at week 14, clinical response, clinical remission, and steroid-free clinical remission at week 52, and mucosal remission and healing at weeks 14 ± 8 and 52 ± 8. Results: Overall, 64 patients with moderate to severe UC were enrolled. The clinical response, clinical remission, and steroid-free clinical remission rates at week 14 were 73.4% (47/64), 65.6% (42/64), and 54.7% (35/64), respectively. Mucosal remission and healing rates at week 14 ± 8 were 64.7% (22/34) and 38.2% (13/34), respectively. A total of 48 patients were treated with VDZ for 52 weeks. Based on intention-to-treat analysis, the clinical response, clinical remission, and steroid-free clinical remission rates at week 52 were 68.8% (44/64), 64.1% (41/64), and 64.1% (41/64), respectively. Mucosal remission and healing rates at week 52 ± 8 were 70.6% (12/17) and 35.3% (6/17), respectively. During the follow-up period, the most common adverse event was skin rash (6/64). No cases of acute infusion reactions, delayed allergic reactions, new hepatitis B infections, active tuberculosis, or malignant tumors were reported. Conclusion: In this single-center retrospective real-world study, the effectiveness of long-term use of VDZ for Chinese patients with UC was similar to the outcomes previously reported in other geographical regions and populations; no new safety signals were found compared with other registered studies.